Performance analysis of reconstructed image using colour demosaicing algorithm for digital images. (8th July 2022) - Devaraj, S. Allwin; Muthukumaran, N.; Jacob, Stalin; Rosita, Jenifer Darling; Vijay, M.M.; Roobert, A. Andrew
Demosaicing algorithm is emerging as one of the most promising techniques in digital image processing because of providing high-quality image enhancement with low power and high speed. Edge detector, weighting block of anisotropic type, and a compensator with filters are the components of the proposed algorithm. Spatial filters and Laplacian methods are used in the filter-based compensation methodology. These improve edge detection, and the blurring effect is reduced. Hardware sharing reduces the cost of the system. Portable and fast systems are required to produce the test results in a short span. For the above-mentioned purpose, the system is designed in VLSI technology. MATLAB and Xilinx tools are used for the system design. A novel strategy to address shading contrasts in multiview video successions is proposed, and it utilises a thick coordinating-based worldwide enhancement structure. The proposed vitality work guarantees to safeguard nearby structures by controlling deviations from the first picture angles. When compared with the existing works 8% and 90.6% of power reduction is observed in the proposed work. It also improves the average colour signal-to-noise ratio quality by more than 1.6 dB.